Some concepts of generalized convex functions (I) - Liana Lupşa; Gabriela Cristescu (Journal of Numerical Analysis and Approximation Theory, 2002)
An extension of the concept of convex function is given in a very general framework provided by a set in which a general convexity for its subsets is defined.